(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive analysis of the concept of cost, its economic essence and main types. The article examines the forming elements of cost, its relationship with material, labor and other costs, as well as such types as full, production and technological cost.